2012
DOI: 10.1002/hep.25529
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid receptor-related orphan receptor α-induced activation of adenosine monophosphate-activated protein kinase results in attenuation of hepatic steatosis

Abstract: There is increasing evidence that the retinoic acid receptor-related orphan receptor a (RORa) plays an important role in the regulation of metabolic pathways, particularly of fatty acid and cholesterol metabolism; however, the role of RORa in the regulation of hepatic lipogenesis has not been studied. Here, we report that RORa attenuates hepatic steatosis, probably via activation of the adenosine monophosphate (AMP)-activated protein kinase (AMPK) and repression of the liver X receptor a (LXRa). First, RORa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 30 publications
(48 reference statements)
7
74
1
Order By: Relevance
“…It was reported that RORα regulated lipid homeostasis in skeletal muscle through upregulation of caveolin-3 and CPT-1α (63). Additionally, activation or overexpression of RORα attenuated hepatic steatosis through AMPK-mediated inhibition of Lxra transcriptional activity (31). Therefore, our present results reveal an additional mechanism that reinforces the effect of RORα on hepatic lipid metabolism.…”
Section: Methodssupporting
confidence: 74%
“…It was reported that RORα regulated lipid homeostasis in skeletal muscle through upregulation of caveolin-3 and CPT-1α (63). Additionally, activation or overexpression of RORα attenuated hepatic steatosis through AMPK-mediated inhibition of Lxra transcriptional activity (31). Therefore, our present results reveal an additional mechanism that reinforces the effect of RORα on hepatic lipid metabolism.…”
Section: Methodssupporting
confidence: 74%
“…GPx1 is a selenocysteine-containing antioxidant enzyme that catalyzes H 2 O 2 -the product of SOD2 action-to H 2 O (23). The treatment of CS increased the protein level of RORa as previously observed (17,18). Similarly, protein levels of SOD2 and GPx1 were increased by CS at less than 1 lM (Fig.…”
Section: Rora Enhances the Transcriptional Expression Of Sod2 And Gpx1supporting
confidence: 69%
“…Several thiourea derivatives, including JC1-40, were demonstrated as activating ligands of RORa that induced activation of AMPK (28). Importantly, the administration of JC1-40 in mice dramatically attenuated hepatic steatosis (18). Further, an observation that hepatic expression level of RORa is significantly decreased when liver injury progresses to steatosis and steatohepatitis in human patients suggests that RORa may have a protective function against progression to NASH (27).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…12,13 Subsequently, 7-oxygenated sterols (7α-hydroxycholesterol, 7β-hydroxycholesterol, 7-ketocholesterol) and (24S)-hydroxycholesterol were identified as novel RORα ligands, with comparable nanomolar binding affinities, 14,15 and recently the structures of synthetic RORα ligands, based on either the benzenesulfonamide or thiourea scaffolds, have been published. [16][17][18] However, no potent and bioavailable ligands are available to date to address important questions about the complex biology of the RORα receptor in vivo. We demonstrate in this work that less conventional approaches, such as the identification of receptor ligands starting from a natural product library of plant extract fractions, are an efficient and effective method to identify potent and bioavailable pharmacological probes to be used for orphan target validation studies.…”
mentioning
confidence: 99%